Analysis of Sanding Parameters, Sanding Force, Normal Force, Power Consumption, and Surface Roughness in Sanding Wood-Based Panels - Bin Luo; Li Li; Hongguang Liu; Meijun Xu; Fangru Xing (BioResources, 2014)
The proper parameters of sanding with an abrasive sanding machine are significant to reduce energy consumption and to improve processing efficiency and quality. The influences of grit size (G), feed speed (U), sanding speed (V), and sanding thickness (Ts) on the sanding force (sF), normal force (nF), arithmetic mean deviation of profile (Ra), power consumption (P), and power efficiency (ε) were analyzed by the orthogonal method in this study. Fuzzy synthetic evaluation (FSE) was adopted to evaluate sF, P, and Ra comprehensively and to determine the optimum sanding parameters. For both medium density fiberboard (MDF) and particle board (PB), G has the greatest impact on Ra. For MDF, Ts and G have great impacts on sF, G is also the significant factor affecting nF, whereas the significant factors affecting P are U and V. For PB, G, U, and Ts have great impacts on sF, while G and Ts are the significant factors for nF. Significant factors for P are V and Ts. For MDF and PB, when the weight vector (sF, Ra) is (0.3, 0.7), the optimum schemes are G80U3m/minV8.04,9.38,10.74m/sTs0.2,0.3mm and G80U3m/minV9.38m/sTs0.2 mm, respectively, and when (sF, Ra) is (0.7, 0.3), the optimum schemes are G80U3,3.72m/minV6.69,8.04,9.38m/sTs0.2 mm and G80U3m/minV8.04,9.38m/sTs0.2 mm, respectively. Additionally, when the weight vector (P, Ra) is (0.3, 0.7) or (0.7, 0.3), the optimum scheme is G100U2.52m/minV5.35m/sTs0.1 mm.